2009
DOI: 10.1007/s12253-009-9188-3
|View full text |Cite
|
Sign up to set email alerts
|

HER2/neu Expression: A Predictor for Differentiation and Survival in Children With Wilms Tumor

Abstract: Wilms tumor is a mixed embroynal neoplasm of the kidney . HER2 is an onco-protein. Its over-expression could be implicated in the development of many tumors. The clinico-demographic and pathological data of 28 Wilms tumor patients were , reviewed. The tissue samples were examined by light Microscopy then immunohistochemical staining for HER2/neu expression. Additional 28 normal surrounding renal tissue specimens were included. There was significant differences between HER2/neu positive and HER2/neu negative Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
2
10
2
Order By: Relevance
“…It has been reported that the HER2 positive rate in RCC is 40% (8). However, other authors have found that the positive rate of HER2 expression was 11% in RCC tissues and was expressed at heterogeneous levels independently of tumor grading and staging (9). Another study reported that the HER2 gene was neither overexpressed nor amplified in cases of Wilms tumor (10).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the HER2 positive rate in RCC is 40% (8). However, other authors have found that the positive rate of HER2 expression was 11% in RCC tissues and was expressed at heterogeneous levels independently of tumor grading and staging (9). Another study reported that the HER2 gene was neither overexpressed nor amplified in cases of Wilms tumor (10).…”
Section: Discussionmentioning
confidence: 99%
“…This is in agree with the results reported by Ghanem et al [3] who suggested that c-erb B2 of no prognostic impact on the clinical outcome of patients and may not play a vital role in the aggressive behavior of WT in a similar study set of patients (previously treated with chemotherapy). In contrast, Salem et al [16] suggested that an over-expression of Her/2 might be associated with a perfect prognosis in WT; (however, it was difficult to conclude that due to few number of cases under study) and Ragab et al [17] who reported a good impact of Her/2 on overall and recurrence free survival of their patients. And before jumping to explain this controversy in the results by the [3] to chemotherapy, we found that the expression pattern of Her/2 among both groups (previously treated vs. previously non treated samples) was similar as mentioned earlier in this report.…”
Section: Discussionmentioning
confidence: 96%
“…Although reports suggested that Her/2 expression in WT is also a marker for epithelial and homologous differentiation and its expression may be a predictor for better overall survival and longer recurrence free survival [16] [17]. However, limited published data are available about the possible variations within the expression patterns of Her/2 in tumors of patients receiving chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,23 However, its use in pediatric solid tumors has been limited. The Her2/Neu targeting mAb, Trastuzumab, was found to be safe when combined with chemotherapy in a phase II trial of newly diagnosed patients with metastatic osteosarcoma.…”
Section: Her2/neumentioning
confidence: 99%